Diaryl vinyl photochromic polyester material as well as preparation method and application thereof
By introducing diaryl ethylene into the polyester structure, diaryl vinyl photochromic polyester material was prepared, which solved the problem that existing colorless anti-counterfeiting invisible toner is not widely used in laser printers, significantly improved the color change speed, color uniformity and color firmness of the toner, and improved the anti-counterfeiting and invisible effects.
Patent Information
- Application Number
- CN202411794486.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-25
AI Technical Summary
The existing colorless anti-counterfeiting invisible toner is not widely used in laser printers. The physical mixing method leads to poor dispersion uniformity of the discoloration functional components, weak substrate adhesion and easy precipitation, which affects the sensitivity and stability of the anti-counterfeiting toner.
By introducing diaryl ethylene (DTE) as a photochromic functional structure and introducing it into the polyester structure through chemical bonding, diaryl vinyl photochromic polyester material was prepared, and anti-counterfeiting invisible toner was prepared in combination with paraffin, charge regulator and flowability enhancer.
It significantly improves the color change speed, color uniformity and color firmness of the toner, improves the anti-counterfeiting and invisibility effects, and solves the problems of poor dispersion uniformity and weak substrate adhesion of the existing toner.
Smart Images

Figure CN119505205A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-counterfeiting invisible toner for laser printing / electrostatic copying, and in particular to a diaryl vinyl photochromic polyester material and a preparation method and application thereof. Background Art
[0002] The rapid development of office automation has made laser printing technology, which has fast paper output, simple toner preparation and use, and low pollution emissions, replace traditional printing methods to a large extent and is widely used in daily life and work. With the emergence of counterfeit and shoddy goods and the prevalence of information security issues, people have put forward higher requirements for printed anti-counterfeiting and invisible materials.
[0003] At present, although colorless anti-counterfeiting invisible toners are used, such as patents CN 112835277 A, CN103645617B, 10039372.0, CN200610097691.7, US6291121, etc., high-quality colorless anti-counterfeiting toners used in laser printers are rare. The preparation of these colorless anti-counterfeiting toners is usually obtained by fully mixing inorganic particles or organic molecules with stimulus-responsive color-changing behaviors such as light, heat, and electricity with resins, waxes, charge control agents, and additives. However, this physical mixing method undoubtedly has problems such as poor dispersion uniformity of color-changing functional components, weak substrate adhesion, and easy precipitation, which seriously affects the sensitivity and stability of the anti-counterfeiting toner.
[0004] Diarylethene (DTE) is a structure with excellent photochromic properties. It is usually composed of two aromatic ring groups connected to a vinyl group. It has typical light-opening and -closing properties and exhibits excellent light stability and fatigue resistance. In the open-ring state, the DTE molecule does not have luminescent properties and has no absorption in the visible light region. This means that in the open-ring state, the DTE molecule is basically colorless. Ultraviolet light can cause DTE to transform from an open-ring state to a closed-ring state. In the closed-ring state, the DTE molecule produces strong absorption in the visible light region and exhibits strong luminescent properties.
[0005] Therefore, research and development of a new type of photochromic polyester material is of great significance for solving the technical problems of poor dispersion uniformity, weak substrate adhesion and easy precipitation of the color-changing functional components in the above-mentioned anti-counterfeiting toner. Summary of the invention
[0006] In view of this, the technical problem to be solved by the present invention is to provide a diaryl vinyl photochromic polyester material and its preparation method and application. The diaryl vinyl photochromic polyester material has a fast color change speed, obvious color contrast before and after color change, good color uniformity, and high color fastness, and can be used to prepare anti-counterfeiting invisible toner.
[0007] In order to achieve the above purpose, the technical solution adopted by the present invention is as follows:
[0008] The present invention provides a diaryl vinyl photochromic polyester material, the structure of which is shown in Formula I:
[0009]
[0010] Wherein, X is selected from O or S atoms, m = 0.9-1,0 <n≤0.1;
[0011] A is selected from any one of the structures shown in formula ac:
[0012]
[0013] In formula c, y is any integer between 4 and 12.
[0014] The diaryl vinyl photochromic polyester material of the present invention has the following interconversion structure under ultraviolet light or visible light:
[0015]
[0016] The structure shown in the above formula Ⅰ-1 produces strong absorption in the ultraviolet or visible light region and exhibits strong luminescence properties.
[0017] The present invention introduces a photochromic functional structure diarylethene (DTE) into a polyester structure by chemical bonding to prepare a diarylethene photochromic polyester material integrating anti-counterfeiting and invisible functions and resin functions.
[0018] The present invention also provides a method for preparing a diaryl vinyl photochromic polyester material, comprising the following steps:
[0019] The compound represented by formula 1-3 is mixed with a catalyst to carry out polymerization reaction to obtain a diaryl vinyl photochromic polyester material represented by formula I;
[0020]
[0021] Preferably, the catalyst is selected from one or more of tetra-n-butyl titanate, antimony acetate, zinc acetate, manganese acetate, and cobalt acetate; more preferably, tetra-n-butyl titanate and zinc acetate.
[0022] Preferably, the molar ratio of the compounds shown in 1-3 is 1:(1.5-2):(0.001-0.01);
[0023] Preferably, the molar ratio of the catalyst to the compound shown in 1 is (0.5-5):1000.
[0024] Preferably, the polymerization reaction temperature is 195°C-260°C;
[0025] Preferably, the polymerization reaction time is 3-8h.
[0026] Preferably, the polymerization reaction is carried out under an inert atmosphere.
[0027] The inert atmosphere is preferably a nitrogen atmosphere.
[0028] The present invention also provides an anti-counterfeiting invisible toner, which comprises the above-mentioned diaryl vinyl photochromic polyester material or the diaryl vinyl photochromic polyester material prepared by the above-mentioned preparation method, paraffin, a charge regulator and a fluidity enhancer as an external additive.
[0029] The present invention uses the above-mentioned diaryl vinyl photochromic polyester material for the preparation of anti-counterfeiting invisible toner, which can significantly improve the color change speed, color uniformity and color fastness of the toner, thereby significantly improving the anti-counterfeiting and invisible effects of the toner.
[0030] The present invention also provides a method for preparing the anti-counterfeiting invisible toner, comprising the following steps:
[0031] (1) melt-mixing a diaryl vinyl photochromic polyester material, paraffin wax, and a charge regulator, extruding, and pulverizing to obtain toner particles with a particle size of 5 to 10 μm;
[0032] (2) The toner particles and the fluidity enhancer additive are mixed to obtain the anti-counterfeiting invisible toner.
[0033] Preferably, the charge regulator is selected from zinc salicylate;
[0034] Preferably, the fluidity enhancer additive is selected from nano-silicon dioxide;
[0035] Preferably, the mass ratio of the diaryl vinyl photochromic polyester material, paraffin wax and zinc salicylate is (85-90):(5-10):(5-10).
[0036] The extrusion in the preparation method is to obtain a compressed tablet by extruding through an extruder.
[0037] The pulverization includes coarse pulverization and air flow pulverization.
[0038] The coarse pulverization is preferably performed using a ball mill, and the air flow pulverization is preferably performed using an air flow pulverizer.
[0039] The preparation method is simple, efficient and suitable for large-scale industrial production.
[0040] The present invention also provides an anti-counterfeiting invisible laser printer or an electrostatic copier, the toner of which is the above anti-counterfeiting invisible toner or the anti-counterfeiting invisible toner prepared by the above preparation method.
[0041] Compared with the prior art, the diarylethene photochromic polyester material provided by the present invention has a structure as shown in Formula I, wherein X is selected from an O or S atom, m = 0.9 - 1, 0 < n ≤ 0.1; A is selected from any one of the structures shown in Formulae a - c; in Formula c, y is any integer between 4 and 12. The diarylethene photochromic polyester material has a tautomeric structure I - 1 under ultraviolet light or visible light irradiation, has strong absorption in the ultraviolet or visible light region, and exhibits strong luminescence properties. The present invention introduces the photochromic functional structure of diarylethene into the polyester structure by means of chemical bonding, so that the diarylethene photochromic polyester material has a fast color change speed, obvious color contrast before and after color change, good color uniformity, and high coloring fastness, and has great application potential in the preparation of anti-counterfeiting invisible toner. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 It is a synthetic route diagram of polyester P - 1 of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0043] In order to further illustrate the present invention, the diarylethene photochromic polyester material provided by the present invention, its preparation method and application will be described in detail below with reference to examples.
[0044] Unless otherwise specified, the following raw materials can be obtained from public commercial channels, and the following methods are conventional methods unless otherwise specified.
[0045] The polyester specifically provided by the present invention has a structure as shown in Formula I:
[0046]
[0047] In Formula I, X is an S atom or an O atom;
[0048] m = 0.9 - 1;
[0049] n = 0 - 0.1;
[0050] A is selected from any one of the following a - c;
[0051]
[0052] In Structure c, y is an integer between 4 and 12.
[0053] (I) Synthesis of Polyester P - 1
[0054] As Figure 1As shown, the synthesis of polyester P-1 whose monomers are terephthalate, hydroquinone and dithiophenecarboxylate-substituted dimethylbutene is taken as a specific example to illustrate the preparation process of the novel anti-counterfeiting invisible toner polyester of the present invention:
[0055] Synthesis of I in route: Under nitrogen protection, titanium tetrachloride (14g, 0.75mol) was slowly added to 200mL of tetrahydrofuran suspended with zinc powder (10g, 0.15mol) pre-cooled to -10°C. Then, a solution of 2,5-dimethyl-3-acetylthiophene (8g, 0.05mol) dissolved in 100mL of tetrahydrofuran was added dropwise. After the reaction mixture was stirred at room temperature for 2 hours, 50mL of 10% potassium carbonate solution was added for hydrolysis, followed by extraction with 300mL of ether three times, and the organic phases were combined. Subsequently, the crude cis product of compound I (20%) was obtained by column chromatography separation and purification. Finally, it was recrystallized with a mixed solvent of n-hexane and ether. 1 H NMR(CDC13)1.90(s,6H),2.00(s,6H),2.27(s,6H),6.07(s,2H); Massspectrum: m / e M + =276.
[0056] Synthesis of compound II: Keep the temperature of the reaction system below 5°C, and slowly drip a solution of α,α-dichlorodimethyl ether (7.3g, 90.1mmol) in dichloromethane (30mL) and a solution of compound I (9.6g, 34.9mmol) in dichloromethane (15mL) into a solution of titanium tetrachloride (33.1g, 19.1mL, 174mmol) in dichloromethane (40mL) at the same time. Keep the mixture warm for 2 hours (until hydrogen chloride gas no longer escapes), slowly heat to room temperature, pour the reactants into ice acidified with hydrochloric acid, separate the organic phase, and dry it with anhydrous magnesium sulfate. Then evaporate the solvent to dryness, and purify by column chromatography to obtain compound II. 1 H NMR (400M, CDC13, ppm): 1.93 (s, 6H), 2.10 (s, 6H), 2.30 (s, 6H), 9.73 (s, 2H); 13 C NMR (100M, CDC13, ppm): 14.9, 15.4, 15.8, 130.8, 136.0, 139.6, 152.0, 153.6, 195.8; Mass spectrum: m / e M + =332.
[0057] Synthesis of compound III: Jones reagent (24 mL) prepared from CrO3 (78 g), deionized water (240 mL) and concentrated sulfuric acid (60 mL) was added to a solution of compound II (1.8 g, 12.9 mmol) in acetone (40 mL) pre-cooled with a water bath under stirring, and the mixture was stirred at room temperature for 6 hours. The solution was then poured out from the green precipitate of chromium trioxide, concentrated to about one-tenth of the initial volume, and the green precipitate was washed with ether. The ether phase and concentrated acetone were then combined and washed with water to remove sulfuric acid. The crude compound III was extracted with a saturated sodium bicarbonate solution and then acidified with concentrated hydrochloric acid to obtain compound III. 1 H NMR (400M, CDCl3, ppm): 1.92 (s, 6H), 2.12 (s, 6H), 2.31 (s, 6H), 12.93 (br, 2H); 13 C NMR (100M, CDCl3, ppm): 14.8, 15.7, 16.2, 131.2, 134.5, 135.7, 148.5, 154.8, 163.8; Mass spectrum: m / e M + =364.
[0058] Synthesis of compound IV: 2 mL of concentrated sulfuric acid was added to a two-necked round-bottom flask loaded with compound III (10.0 g, 78.0 mmol) and 70 mL of methanol, and the mixture was heated to reflux overnight. After cooling to room temperature, the mixture was poured into 200 mL of water and extracted with ethyl acetate (100 mL × 3). The organic phase was combined, dried over anhydrous magnesium sulfate, and purified by column chromatography to obtain colorless compound IV. 1 H NMR (400M, CDCl3, ppm): 1.92 (s, 6H), 2.12 (s, 6H), 2.31 (s, 6H), 4.02 (s, 6H); 13 C NMR (100M, CDCl3, ppm): 14.8, 15.4, 16.3, 52.2, 131.5, 134.2, 135.5, 148.5, 154.8, 160.5; Mass spectrum: m / e M + =392.
[0059] Synthesis of polyester P-1: Dimethyl terephthalate (200 mmol), hydroquinone (360 mmol), tetrabutyl titanate (0.1 mmol), anhydrous zinc acetate (0.11 mmol) and dimethylbutene substituted with dithiophene carboxylate (12 mmol) were added to a four-necked flask. After reacting at 195°C for 3 hours under a nitrogen atmosphere, the amount of methanol released reached the theoretical value. The temperature was raised to 260°C, and the nitrogen protection was removed. The system was evacuated with a vacuum pump. After reaching the temperature and vacuum requirements, the polymerization reaction continued to proceed in the forward direction. When the polymer was observed to have a climbing phenomenon, the melt was poured out and cooled rapidly to obtain a diaryl vinyl polyester sample No. 1. The molecular weight Mn tested by gel permeation chromatography (GPC) was 5.38 kg mol -1 , the polydispersity index PDI is 1.87. Infrared spectrum test (KBr, cm -1 ): 1107cm -1 The stretching vibration of COC of the ester bond; 1250cm -1 The symmetrical stretching vibration of CO single bond of phenol; 1457 cm -1 Vibration of benzene ring skeleton; 1707cm -1 It is the C=O stretching vibration of the ester bond. Raman spectrum test (excitation wavelength is 514nm): 1460cm -1 It is the characteristic absorption peak of C=C.
[0060] Preparation steps of anti-counterfeiting invisible toner:
[0061] (1) Mixing polyester material, paraffin wax and zinc salicylate uniformly in a high-speed mixer according to a certain mass ratio;
[0062] (2) After high-temperature melting and mixing, the mixture is extruded and pressed into tablets, and then coarsely crushed, and further crushed and classified by a jet mill to obtain a toner with a suitable particle size;
[0063] (3) The powder is mixed evenly with nano titanium dioxide powder (by mass or molar ratio) to obtain a toner with anti-counterfeiting and invisible function suitable for laser printing / electrostatic copying.
[0064] (II) Preparation of No. 1-7 Toner
[0065] Example 1
[0066] Polyester P-1, paraffin wax and zinc salicylate are uniformly mixed in a high-speed mixer at a mass ratio of 85:5:10, and then melt-mixed at high temperature, extruded and tableted, and then coarsely crushed, and further crushed and classified by a jet mill to obtain a No. 1 toner of 5 to 10 μm; the powder is uniformly mixed with nano titanium dioxide powder (mass ratio of 100:(0.1 to 2)) to obtain a No. 1 toner with anti-counterfeiting and invisible function suitable for laser printing / electrostatic copying.
[0067] The structure of polyester P-1 is shown below:
[0068]
[0069] Example 2
[0070] The same as Example 1, except that polyester P-1 is replaced by "polyester P-2", the preparation process of polyester P-2 is the same as that of polyester P-1, except that the monomer hydroquinone is replaced by bisphenol A. Finally, a No. 2 toner with anti-counterfeiting invisible function suitable for laser printing / electrostatic copying is obtained.
[0071] The structure of polyester P-2 is shown below:
[0072]
[0073] Example 3
[0074] The same as Example 1, except that the polyester P-1 is replaced by "polyester P-3", the preparation process of the polyester P-3 is the same as that of the polyester P-1, except that the monomer hydroquinone is replaced by butanediol. Finally, a No. 3 toner with anti-counterfeiting invisible function suitable for laser printing / electrostatic copying is obtained.
[0075] The structure of polyester P-3 is shown below:
[0076]
[0077] Example 4
[0078] The same as Example 1, except that polyester P-1 is replaced by "polyester P-4", the preparation process of polyester P-4 is the same as that of polyester P-1, except that methyl dicarboxylate of dithienylethylene is replaced by methyl dicarboxylate of difuranylethylene. Finally, No. 4 toner with anti-counterfeiting invisible function suitable for laser printing / electrostatic copying is obtained.
[0079] The structure of polyester P-4 is shown below:
[0080]
[0081] Example 5
[0082] The same as Example 4, except that the molar number of difuranylethylene diformate methyl ester was changed to 20 mmol during the preparation of the polyester P-4. Finally, a No. 5 toner with anti-counterfeiting and invisible function suitable for laser printing / electrostatic copying was obtained.
[0083] Comparative Example 1
[0084] The same as Example 1, except that the reactant dithienylethylene diformate was not added during the preparation of polyester P-1. Finally, No. 6 toner was obtained.
[0085] Comparative Example 2
[0086] The same as Example 1, except that the reactant dithienylethylene diformate was not added in the process of preparing polyester P-1, but dithienylethylene diformate was physically mixed with the obtained polyester, paraffin wax and zinc salicylate in the process of preparing toner. Finally, No. 7 toner was obtained.
[0087] (III) Performance test (1) Toner color change performance test
[0088] The color change performance of the toner of the present invention is tested using an SHG-200 ultraviolet lamp. The wavelength of the light source is 365nm, the power is 200W, the vertical distance between the paper and the light source is 10cm, and the paper gradually shows blue fonts after being irradiated by the light source.
[0089] (2) Evaluation of fixing strength:
[0090] The fixing strength test refers to GB / T 29300-2012.
[0091] The fixing strength was evaluated according to the following criteria:
[0092] Excellent: firmness ≥93%;
[0093] Good: firmness 90% to 93%;
[0094] Poor: firmness <90%.
[0095] (3) Color change sensitivity test:
[0096] The paper printed with the prepared toner is transferred from natural light to a sealed ultraviolet light, and the time required for the blue font to appear is tested to evaluate the color change sensitivity of the toner.
[0097] Excellent: Color change time is less than 1 minute
[0098] Good: Color change time is less than 5 minutes
[0099] Poor: Color change time is greater than 10 minutes
[0100] (4) Color change uniformity test:
[0101] Transfer the paper printed with the prepared toner from natural light to a sealed ultraviolet light, and observe whether the clarity of the blue font is uniform.
[0102] Good: All the words are clearly visible
[0103] Good: The writing is basically clear, but there are occasional breaks.
[0104] Poor: The writing is not clear
[0105] Contrast test before and after color change:
[0106] The paper printed with the prepared toner was transferred from natural light to a sealed ultraviolet light, and the clarity of the blue font was tested to evaluate the contrast before and after the toner color change.
[0107] Pros: Very clear font
[0108] Good: The font is clearer
[0109] Bad: Blurred fonts
[0110] The above performance test results are shown in Table 1, which is the performance evaluation test results of the anti-counterfeiting invisible toner prepared in Examples 1-5 and Comparative Examples 1-2.
[0111] Table 1 Performance evaluation test results of anti-counterfeiting invisible toner prepared in Examples 1-5 and Comparative Examples 1-2
[0112]
[0113]
[0114] The results in Table 1 show that within the range of the components and proportions of the present invention, the quality evaluation of the samples actually printed by the toner prepared by the present invention meets the standard requirements. The test data of Examples 1-5 and Comparative Examples 1-2 in Table 1 show that the toner without the introduction of photochromic functional groups into the polyester does not have the anti-counterfeiting invisible printing function; the photochromic groups are not bonded to the polyester through chemical bonds, but are directly mixed into the mixture of resin and other components in the preparation of the toner, and its fixing strength, color uniformity, color change sensitivity, and color contrast before and after color change are all poor.
[0115] The above embodiments are only used to help understand the method and core idea of the present invention. It should be noted that, for those skilled in the art, several improvements and modifications can be made to the present invention without departing from the principles of the present invention, and these improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A diaryl vinyl photochromic polyester material, characterized in that: Its structure is shown in Formula I: Wherein, X is selected from O or S atoms, m = 0.9-1,0 <n≤0.1; A is selected from any one of the structures shown in formula ac: In formula c, y is any integer between 4 and 12.
2. The diaryl vinyl photochromic polyester material according to claim 1, characterized in that: The diaryl vinyl photochromic polyester material has the following interconversion structure under ultraviolet light or visible light:
3. A method for preparing a diaryl vinyl photochromic polyester material, characterized in that: The following steps are involved: The compound represented by formula 1-3 is mixed with a catalyst to carry out polymerization reaction to obtain a diaryl vinyl photochromic polyester material represented by formula I; 4. The preparation method according to claim 3, characterized in that: The catalyst is selected from one or more of tetra-n-butyl titanate, antimony acetate, zinc acetate, manganese acetate, and cobalt acetate.
5. The preparation method according to claim 3, characterized in that: The molar ratio of the compound shown in 1-3 is 1:(1.5-2):(0.001-0.01); The molar ratio of the catalyst to the compound shown in 1 is (0.5-5):1000.
6. The preparation method according to claim 3, characterized in that: The polymerization temperature is The polymerization reaction time is 3-8h.
7. An anti-counterfeiting invisible toner, characterized in that: The invention comprises the diaryl vinyl photochromic polyester material according to any one of claims 1 to 2 or the diaryl vinyl photochromic polyester material prepared by the preparation method according to any one of claims 3 to 6, paraffin, a charge regulator and a fluidity enhancer as an external component.
8. The method for preparing the anti-counterfeiting invisible toner according to claim 7, characterized in that: The following steps are involved: (1) The diaryl vinyl photochromic polyester material, paraffin wax, and charge regulator are melt-mixed, extruded, and crushed to obtain a particle size of Toner particles; (2) The toner particles and the fluidity enhancer additive are mixed to obtain the anti-counterfeiting invisible toner.
9. The method for preparing the anti-counterfeiting invisible toner according to claim 8, characterized in that: The charge regulator is selected from zinc salicylate; The fluidity enhancer additive is selected from nano silicon dioxide; The mass ratio of the diaryl vinyl photochromic polyester material, paraffin wax and zinc salicylate is (85-90):(5-10):(5-10).
10. An anti-counterfeiting invisible laser printer or electrostatic copier, characterized in that: The toner is the anti-counterfeiting invisible toner described in claim 7 or the anti-counterfeiting invisible toner prepared by the preparation method described in claim 8 or 9.
Citation Information
Patent Citations
Color fluorescent anti-counterfeiting invisible toner and preparation method
CN103645617B
Durable false-proof colorless carbon powder used for laser printer and its preparing method
CN1967390A
Fluorescent treated external surface additives for toner
US6291121B1